Traditional Cultural Practices and its Changing Landscape in the Alaknanda Valley, Garhwal Himalaya - Vishwambhar Prasad Sati (Culture & Society: Journal Of Anthropological Research, 2026)
The Alaknanda Valley has a rich cultural heritage. It is home to the Panch Badris, Panch Kedars, and Panch Prayags. Additionally, it is renowned for the Dwadas Jyotirlinga and Shakti Peeth. Known as 'Dev Bhumi,' it is considered the land of Gods and Goddesses. People worship various forms of nature, including trees, water, and land, along with all folk deities. They celebrate fairs and festivals throughout the year, aligning with the changing seasons and the sun's position in the northern and southern hemispheres. This study illustrates the rich cultural heritage of the Alaknanda Valley and its evolving landscape. This is a field-based empirical and observational study, and the author employed a qualitative approach. He visited the entire Alaknanda valley, participated in numerous cultural events, and interviewed 10 priests and 100 local people, who are engaged in practicing culture and rituals. Data were also collected though literature review and secondary sources. The findings of this study indicate that the traditional cultural heritage of the Alaknanda Valley underwent significant decline during the 1980s. This situation persisted until 2010, after which efforts to restore cultural traditions began. At present, the region's rich cultural heritage has been largely revived to its pre-1980s state. Local people play a crucial role in preserving cultural practices by actively participating in the celebration of fairs and festivals every month. The culture of the Alaknanda Valley is deeply connected to nature and its conservation. Therefore, maintaining this rich cultural heritage requires its continued practice in traditional ways.